Overworked? An Observation of the Relationship Between Student Employment and Academic Performance. (November 2016) - Logan, Jennifer; Hughes, Traci; Logan, Brian
Current observations from the National Center for Education Statistics demonstrate the dramatic increase in college student employment over the past few decades. Not only are more students employed than in previous decades, students are working more hours. This could lead to declines in academic performance as hours worked increase, resulting in less time for studying. This article correlates the number of hours worked with each student's academic performance. Data used in the article are taken from student responses to the College Student Experience Questionnaire developed by the Indiana University at Bloomington. This analysis looks at differences regarding students employed in on-campus jobs relative to off-campus jobs. Various relationships are estimated, breaking down the sample by various cohorts including class, gender, and age. Estimated findings show that students should be discouraged from working over 20 hours in off-campus jobs in their first 2 years of college.